2015
DOI: 10.2214/ajr.14.12776
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution 3-T MRI of the Fingers: Review of Anatomy and Common Tendon and Ligament Injuries

Abstract: OBJECTIVE. With high-resolution 3-T MRI, the complex anatomy of the fingers can be imaged in exquisite detail to provide an accurate diagnosis of clinically important ligament and tendon injuries. CONCLUSION. We present our 3-T MRI protocol using a dedicated hand-and-wrist coil and review normal MRI anatomy of the fingers. We emphasize a systematic approach to the interpretation of finger MRI examinations and illustrate this approach with examples of tendon and ligament abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 44 publications
0
34
0
Order By: Relevance
“…Additionally, tendons build so-called functional entheses with associated ligamentous structures, such as flexor tendon pulleys [11]. These pulleys have a fibrocartilaginous component and discontinuously wrap around the flexor tendons preventing their bowstringing during flexion [12]. Recent studies have shown that inflammation and thickening of flexor tendon pulleys are potentially due to mechanical stress ("deep Koebner response") and may lead to the initial development of flexor tenosynovitis and dactylitis, that are major features of PsA [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, tendons build so-called functional entheses with associated ligamentous structures, such as flexor tendon pulleys [11]. These pulleys have a fibrocartilaginous component and discontinuously wrap around the flexor tendons preventing their bowstringing during flexion [12]. Recent studies have shown that inflammation and thickening of flexor tendon pulleys are potentially due to mechanical stress ("deep Koebner response") and may lead to the initial development of flexor tenosynovitis and dactylitis, that are major features of PsA [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…When imaging the thumbs, coronal and sagittal views should be tilted 90° to sesamoids at the level of the metacarpophalangeal joint (Figure 3) [13]. It is always important to include adjacent fingers within the field of view of the image for comparison [14]. Three-Tesla MRIs are preferred due to the high resolution and detail provided for these small anatomical regions.…”
Section: Hand/wrist 41 Mri Protocolmentioning
confidence: 99%
“…These measurements help plan derotational osteotomy and evaluate therapy results. 47 Magnetic Resonance Imaging MRI is extremely valuable in evaluating traumatic soft tissue injuries of the hand and fingers 48 and is able to diagnose accurately the extent of tendon, ligament, and other soft tissue injury. 46 Tendons, ligaments, and volar plates have a homogeneous low signal on T1-weighted, T2-weighted, and PD sequences.…”
Section: Computed Tomographymentioning
confidence: 99%